Role of Humic-Bound Iron as an Electron Transfer Agent in Dissimilatory Fe(III) Reduction - Lovley, Derek R. (American Society for Microbiology, 1999)
The dissimilatory Fe(III) reducer Geobacter metallireducens reduced Fe(III) bound in humic substances, but the concentrations of Fe(III) in a wide range of highly purified humic substances were too low to account for a significant portion of the electron-accepting capacities of the humic substances. Furthermore, once reduced, the iron in humic substances could not transfer electrons to Fe(III) oxide. These results suggest that other electron-accepting moieties in humic substances, such as quinones, are the important electron-accepting and shuttling agents under Fe(III)-reducing conditions.